The Effect of Mental Spiritual Guidance on Self-Acceptance Among Single Mothers in Gampong Mon Geudong - Desy Murni Lasari; Mutiara Zatil Aqmar; Minda Septiani (Universitas Negeri Medan, 2025)
This study discusses the influence of mental and spiritual guidance on self-acceptance among single mothers in Gampong Mon Geudong, Lhokseumawe City. Self-acceptance among single parents varies. Since single parents face different challenges, some struggle to accept themselves as single mothers, seek pleasure for themselves, disrupt others' households, or experience mental health issues. The objective of this study is to determine whether there is an influence of spiritual and mental guidance on self-acceptance among single parents. The type of research used is descriptive quantitative. The population consists of 25 single parents. The sample used in this study was obtained using the Nonprobability Sampling technique with saturated sampling. The researcher used this sampling technique because the sample size was 25 people. Saturated sampling is conducted when the population is less than 30 people. The data analysis technique used was simple linear regression. The results of this study indicate that spiritual guidance falls into the moderate category, while self-acceptance among single mothers also falls into the moderate category. There is a positive influence of spiritual guidance on self-acceptance, meaning that the hypothesis of this study is accepted. The influence is 32.9%, with the remaining percentage influenced by other factors not investigated in this study.